Computer Science in French Universities: Early Entrants and Latecomers. - Mounier-Kuhn, Pierre (Information & Culture, 2012)
This paper offers a historical model of the development of a new science in higher education. Comparing case studies in computer science in French universities during the 1950s and 1960s, the author argues that only a specific configuration of high-level teaching, of early research and of practical applications, could achieve a "critical mass" necessary to promote and legitimize a new discipline. Concepts of path-dependency and bifurcations are used to explain how some universities reached international status in this field, while others lagged behind. The conclusion suggests a transnational comparison.